Case Report: Dropped head syndrome as a main clinical sign of suspected myasthenia gravis in two dogs - Reyes, Henry Mendo; Galli, Greta; Fiorentino, Erica; Gardini, Anna; Bravaccini, Beatrice; Menchetti, Marika (Frontiers in Veterinary Science, 2025)
Drop head syndrome (DHS), characterized by pronounced cervical ventroflexion, is a clinical syndrome that can be found associated with neuromuscular disorders, particularly myasthenia gravis. In this case series, we describe two dogs, an 8-year-old Basset Hound and a 3-year-old Zwergpinscher, presenting with DHS as the main clinical sign. In both cases, a presumptive diagnosis of myasthenia gravis was made and were empirically treated with pyridostigmine. Telephone follow-ups at 6 and 4 months after diagnosis, respectively, were consistent with clinical remission. These cases highlight the diagnostic challenges of DHS, emphasizing the need for thorough evaluation to exclude numerous differential diagnoses. In cases where myasthenia gravis is strongly suspected despite negative tests, trial treatment with anti-cholinesterase drugs may be considered, with caution to avoid potential side effects.